Arthropod remains in the oral cavities of fossil reptiles support inference of early insectivory - Modesto, Sean P. (The Royal Society, 2009)
Inference of feeding preferences in fossil terrestrial vertebrates (tetrapods) has been drawn predominantly from craniodental morphology, and less so from fossil specimens preserving conclusive evidence of diet in the form of oral and/or gut contents. Recently, the pivotal role of insectivory in tetrapod evolution was emphasized by the identification of putative insectivores as the closest relatives of the oldest known herbivorous amniotes. We provide the first compelling evidence for insectivory among early tetrapods on the basis of two 280-million-year-old (late Palaeozoic) fossil specimens of a new species of acleistorhinid parareptile with preserved arthropod cuticle on their toothed palates. Their dental morphology, consisting of homodont marginal dentition with cutting edges and slightly recurved tips, is consistent with an insectivorous diet. The intimate association of arthropod cuticle with the oral region of two small reptiles, from a rich fossil locality that has otherwise not produced invertebrate remains, strongly supports the inference of insectivory in the reptiles. These fossils lend additional support to the hypothesis that the origins and earliest stages of higher vertebrate evolution are associated with relatively small terrestrial insectivores.